2018
DOI: 10.1002/jcb.27905
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA‐p21 enhances the sensitivity of radiotherapy for gastric cancer by targeting the β‐catenin signaling pathway

Abstract: Long noncoding RNAs (lncRNAs) are a large and diverse class of transcribed RNA molecules with a length of more than 200 nucleotides that modulate the gene expression at the posttranscriptional or transcriptional level. LncRNAs played crucial roles in many biological processes, such as cell proliferation, metastasis, and migraton. In this study, we evaluated the role of lincRNA‐p21 in the gastric cancer (GC). We demonstrated that the expression level of lincRNA‐p21 was downregulated in the GC tissues and cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Levels of β-catenin and its target genes, c-MYC and Cyclin D1, were also downregulated upon lincRNA-p21 overexpression, as well as upon IR in CRC [100]. Inhibition of the β-catenin pathway abolished the effects of lincRNA-p21 overexpression on cell proliferation and radiosensitivity in gastric cancer cells [99]. This supports the role of lincRNA-p21 in promoting radiosensitivity by inhibiting the Wnt/β-catenin pathway.…”
Section: Lncrnassupporting
confidence: 57%
See 1 more Smart Citation
“…Levels of β-catenin and its target genes, c-MYC and Cyclin D1, were also downregulated upon lincRNA-p21 overexpression, as well as upon IR in CRC [100]. Inhibition of the β-catenin pathway abolished the effects of lincRNA-p21 overexpression on cell proliferation and radiosensitivity in gastric cancer cells [99]. This supports the role of lincRNA-p21 in promoting radiosensitivity by inhibiting the Wnt/β-catenin pathway.…”
Section: Lncrnassupporting
confidence: 57%
“…A handful of lncRNAs have been linked to IR response by regulating the Wnt/β-catenin pathway. lincRNA-p21 was downregulated in gastric cancer and CRC cells and tissues [99,100]. Ectopic overexpression of lincRNA-p21 enhanced radiosensitivity and inhibited the Wnt/β-catenin pathway in both tumor types.…”
Section: Lncrnasmentioning
confidence: 96%
“…Furthermore, it has been elucidated that lncRNAs modulate the radioresistance of tumors through modulating gene expression, 32 and signaling pathways against radiotherapy in tumors. 21,33,34 Thereupon, we attempted to explore the association between LINC00511 and JAK2/STAT3 signaling pathway. Our paper displayed that LINC00511 regulated JAK2/ STAT3 signaling pathway and JAK2 expression was upregulated when given 4Gy irradiation in thyroid carcinoma, where the association of JAK2/STAT3 signaling pathway with radioresistance was probed for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The Janus kinase (JAK)2/signal transducer and activator of transcription (STAT)3 signaling pathway is constitutively stimulated at high level, and regulates the expression of various genes as well as physiological functions in tumors. [17][18][19] Despite multiple reports have claimed the radioresistant effect of signaling pathways on tumors, 20,21 the function of JAK3/ STAT3 signaling pathway in the radioresistance of carcinomas is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they showed that ectopic expression of lincRNA-p21 suppressed β-catenin and c-myc expression. Overexpression of lincRNA-p21 inhibited the GC cell proliferation and increased the radiosensitivity of GC cells by regulating the Wnt/β-catenin signaling pathway, the activation of which is one of the most common features of GC [113].…”
Section: Gastric Cancermentioning
confidence: 99%